Small-Scale Energy Harvesting 2012
DOI: 10.5772/51360
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Conversion for Vibration Energy Harvesting

Abstract: This chapter focuses on vibration energy harvesting using electrostatic converters. It synthesizes the various works carried out on electrostatic devices, from concepts, models and up to prototypes, and covers both standard (electret-free) and electret-based electrostatic vibration energy harvesters (VEH).After introducing the general concept of Vibration Energy Harvesting and the global advantages and drawbacks of electrostatic devices to convert mechanical power into electricity ( §1), we present in details … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
142
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 41 publications
4
142
0
2
Order By: Relevance
“…The layer is then left to cool down to maintain an electric field. This allows the dipoles of the dielectric layer to be oriented in the same direction as the electric field [1], as shown in Fig. 3.…”
Section: Electrostatic Harvester Conversion Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…The layer is then left to cool down to maintain an electric field. This allows the dipoles of the dielectric layer to be oriented in the same direction as the electric field [1], as shown in Fig. 3.…”
Section: Electrostatic Harvester Conversion Mechanismsmentioning
confidence: 99%
“…Therefore, the authors suggested that the air gap must be controlled precisely and minimized to achieve high capacitances. Moreover, it is also important to prevent from electrical breakdown problems [1].…”
Section: Comparative Studies Of Capacitor Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the standby mode a typical energy demand is estimated to be up to a dozen μW, whereas in the measurement mode the demand can be either small or very large -from 0.1 μW to 100 mW during communication. These values of energy can be supplied by an efficient power supply in a sensor node based only on EH [16]. The rectifier, buffer, and stabilizer systems must have a high energy efficiency.…”
Section: Possible Sources Of Energy Used In the Eh Assessment Of Thementioning
confidence: 99%
“…They both start when the converter's capacitance is maximal. At this point, a charge is injected into the capacitor thanks to an external source, to polarize it [3].…”
Section: Introductionmentioning
confidence: 99%